STRATEGI PENGAWASAN OLEH KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP NEGERI 02 MARISA - Sya'ban, Riska (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study aims to describe the implementation of educational supervision by the principal at SMP Negeri 2 Marisa, focusing on academic supervision, teacher performance evaluation, as well as the challenges and strategies in its execution. The research employs a qualitative approach with in-depth interview techniques conducted with the principal. The findings indicate that the principal carries out supervision through classroom observations, monthly evaluations, and post-supervision reflections directly with teachers. Evaluations are conducted regularly, and follow-ups are monitored to ensure continuous improvement and sustainability of teaching quality. Despite challenges such as the implementation of the Merdeka Curriculum and the use of digital assessment systems, the principal effectively adapts supervision through the establishment of teacher learning communities. This study emphasizes the crucial role of school leadership in enhancing educational quality through continuous and contextual supervision.